(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The management of exit temperature in gas turbine combustors is critical for ensuring turbine blade life, thermal efficiency, and operational flexibility. Dilution air injection is a primary method for cooling combustion products, yet the quantitative effect of modulating its flow rate on exit temperature remains insufficiently understood. This study employs a Computational Fluid Dynamics (CFD) approach using ANSYS FLUENT to investigate the impact of dilution air flow rate modulation on the exit temperature of a can‑type gas turbine combustion chamber operating under steady‑state conditions with methane fuel. A three‑dimensional model of the combustor was developed, and simulations were performed for dilution air mass flow rates ranging from 0.001 kg/s to 0.005 kg/s. Results show a strictly monotonic decrease in exit temperature with increasing dilution air flow, yielding a total reduction of 87 °C (approximately 4.0%) across the tested range. However, diminishing marginal cooling effectiveness is observed, with the largest reduction (43 °C) occurring between 0.001kg/s and 0.002 kg/s and progressively smaller reductions at higher flow rates. The midpoint exit temperature decreases by about 20 °C when dilution air is increased from 100% to 400% of baseline. The study quantitatively demonstrates that while increased dilution air flow significantly reduces thermal loading, benefits diminish beyond an optimal range (approximately 0.003–0.004 kg/s or a 200–250% increase). These findings provide design engineers with quantitative criteria for balancing exit temperature reduction against pressure loss, combustion efficiency, and flame stability.